Jewish travellers - Eisenstein, Judah David, 1854-1956; Adler, Elkan Nathan, 1861-1946 (Routledge Curzon, 2005)
First published in 1930. The wandering Jew is a very real character in the great drama of history. He has travelled as nomad and settler, as fugitive and conqueror, as exile and colonist and as merchant and scholar. Of necessity bilingual and therefore the master of many languages, the Jew was the ideal commercial traveller and interpreter.Based on the volume of 24 Hebrew texts of Jewish travellers by J D Eisenstein, this volume begins with the ninth century. After the sixteenth century geographical discoveries had made the whole world familiar to most people. Consequently, the wandering J.
The texts and notes are in large part translated from J.D. Eisenstein's Ozar massaoth ("Treasure of travel"), a collection of 24 Hebrew texts. "[The present collection] begins with the ninth and ends in the middle of the eighteenth century ... The main object ... has been to give a conspectus of Jewish travel during the middle ages." cf. Pref.
Originally published in 1930.
Keywords: Voyages and travels.; Travel, Medieval.; Palestine -- Description and travel.; Voyages.; Voyage -- Histoire -- 500-1500 (Moyen Âge); journeys.; TRAVEL -- Museums, Tours, Points of Interest.; TRAVEL -- Hikes & Walks.; TRAVEL -- Budget.; TRAVEL -- Special Interest -- Ecotourism.; TRAVEL -- Parks & Campgrounds.; TRAVEL -- Reference.; TRAVEL -- Road Travel.; TRAVEL -- Special Interest -- Adventure.; Travel; Travel, Medieval; Voyages and travels; Middle East -- Palestine